THE IMPACT OF PROFESSIONAL DEVELOPMENT PROGRAMS ON TEACHERS’ PEDAGOGICAL SKILL AND STUDENT ACADEMIC PERFORMANCE IN SECONDARY SCHOOLS IN BALOCHISTAN, PAKISTAN - Dr. Najeeb Ullah; Muhammad Hassan Veesar; Farzana Jabeen Khoso; Mahwish Saleem Shaikh; Assan Das; Dr. Zubair Ahmed Chachar (International Journal of Contemporary Issues in Social Sciences, 2024)
The Education Department in Balochistan aims to enhance educational value by raising teaching standards and promoting ongoing professional development for teachers. Despite the growing literature linking professional development and professional knowledge to student outcomes, the specific impact on teaching and learning remains unclear. This study examines the effect of teachers’ professional development on academic performance in Balochistan’s secondary schools, focusing on the arbitrating role of teachers’ specialized understanding. A survey collected data from 350 teachers from various public secondary schools in the Makran division. The findings revealed a significant positive correlation between professional development programs, teacher professional knowledge, and students’ academic performance (r =.649, p<.01). Participation in professional development programs was strongly associated with increased teacher professional knowledge and enhanced student academic performance. Additionally, professional development’s impact on students’ academic performance correlated positively with both professional development programs (r =.292, p<.01) and teacher professional knowledge and students’ academic performance (r =.403, p<.01). The study determined that proficient improvement contributes to improved student academic outcomes by enhancing teachers’ professional knowledge and competencies. It recommends encouraging teachers to participate in diverse professional development endeavours.